2009
DOI: 10.1002/ange.200901277
|View full text |Cite
|
Sign up to set email alerts
|

Phosphonium Salts as Chiral Phase‐Transfer Catalysts: Asymmetric Michael and Mannich Reactions of 3‐Aryloxindoles

Abstract: Chiraler PTC: Eine hoch effiziente asymmetrische Michael‐Addition von 3‐Aryloxindolen gelang mit einem Tetraalkylphosphoniumsalz als chiralem Phasentransferkatalysator (PTC). Die Produkte wurden in nahezu quantitativen Ausbeuten und mit hohen ee‐Werten erhalten. Derselbe Katalysator vermittelte auch eine asymmetrische Mannich‐Reaktion von 3‐Aryloxindolen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
3

Year Published

2010
2010
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(28 citation statements)
references
References 67 publications
0
25
0
3
Order By: Relevance
“…Maruoka and co-workers have shown that C 2 -symmetric tetraalkyl phosphonium salt 6 is an effective phase-transfer catalyst for catalytic enantioselective amination, [30] Michael, [31] and Mannich reactions. [31] Ooi and co-workers accomplished the enantioselective alkylation of azlactones with N -benzylated D 2 -symmetric P -spiro tetraaminophosphonium salt 7 under phase-transfer conditions. [32] …”
Section: Chiral Cation-directed Catalysismentioning
confidence: 99%
“…Maruoka and co-workers have shown that C 2 -symmetric tetraalkyl phosphonium salt 6 is an effective phase-transfer catalyst for catalytic enantioselective amination, [30] Michael, [31] and Mannich reactions. [31] Ooi and co-workers accomplished the enantioselective alkylation of azlactones with N -benzylated D 2 -symmetric P -spiro tetraaminophosphonium salt 7 under phase-transfer conditions. [32] …”
Section: Chiral Cation-directed Catalysismentioning
confidence: 99%
“…The other oxindoles were prepared according to the literature and references therein. [11][12][13][14][15][16] The N,N'-dioxide ligands were prepared according to the literature. [19] General procedure for the enantioselective a-amination of 3-substituted oxindoles with azodicarboxylates: N,N'-dioxide L6 (4.9 mg, 0.0075 mmol), scandium triflate (2.5 mg, 0.005 mmol), 3-methyloxindole (1 a; 14.7 mg, 0.10 mmol), and 4 molecular sieves (5 mg) were stirred in a dry reaction tube in CH 2 Cl 2 (1.0 mL) under nitrogen at 30 8C for 0.5 h and then cooled to À20 8C, at which point diisopropylazodicarboxylate (2 a; 20 mL, 0.1 mmol) was added.…”
Section: Methodsmentioning
confidence: 99%
“…[9] Furthermore, the application of prochiral 3-substituted oxindoles as nucleophiles provides a very simple and straightforward approach for the synthesis of optically active 3-amino-2-oxindole derivatives with a chiral quaternary center, and studies in this field have received special attention because oxindoles bearing C3-quaternary structures are widely distributed in a number of natural products and pharmaceutical molecules. [10] Several catalytic asymmetric reactions of 3-substituted oxindoles, including the aldol reaction, [11] conjugate addition reaction, [12] Mannich reaction, [13] fluorination, [14] and other types of reaction, [15] have been successively reported. However, relatively fewer examples have been documented for catalytic asymmetric a-amination of oxindoles, which is very useful for the generation of quaternary 3-amino-2-oxindole alkaloid compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, great effort has been devoted to the asymmetric reactions of nucleophilic 3-substituted oxindoles [1][2][3][4][5] to construct oxindoles containing an asymmetric quaternary stereogenic center [6] at the C3 position. These compounds have potential medicinal interest, owing to the unique biological activities of such natural products.…”
Section: Introductionmentioning
confidence: 99%